Open access to European academic courses supported by the ASK-CDM-ECTS tool - Sampson, Demetrios; Zervas, P. (2012)
Within the context of the emerging Open Academic Courses Initiatives, the issue of explicitly describing an academic course is raised. Nevertheless, existing Initiatives do not share a common conceptual model for describing their academic courses. The main drawback of this approach is that these descriptions impede inter initiative comparison and exploitation of academic courses by students and course tutors. The Course Description Metadata (CDM) specification has been proposed as a way to describe academic courses in a common format. Within the context of European Higher Education, CDM specification has been influenced by the European Credit Transfer Accumulation System (ECTS). As a result, an application profile of the CDM specification has been developed referred to as CDM-ECTS. Despite these efforts, it appears that there are not software tools that allow authoring of academic courses descriptions following the CDM-ECTS application profile. Thus, in this paper we target to address this issue by introducing a web-based tool, namely ASK-CDM-ECTS. © 2012 IEEE.